1983
DOI: 10.1111/1523-1747.ep12555351
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Histamine Metabolism in Mastocytosis

Abstract: The urinary excretion of histamine and its main metabolite, 1-methyl-4-imidazoleacetic acid (MeImAA), was determined in 30 adult patients with the clinical diagnosis of urticaria pigmentosa (UP). Clinical and laboratory investigations including skin histology, bone marrow examination, and scintigraphy of the skeleton, liver, and spleen revealed systemic manifestations in 14 cases. Among the 16 cases with dermal proliferation of mast cells only 3 cases classified as telangiectasia macularis eruptiva perstans (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 27 publications
1
44
0
1
Order By: Relevance
“…measurements of mast cell mediators, should be sought in mastocytosis, but random analysis of the urinary histamine levels was not proven useful for establishing the diagnosis. Only 1–3% of histamine appears unmetabolized in the urine, but there may be an increase in the major urinary histamine metabolites, N T -methyl-histamine and 1-methyl-4-imidazoleacetic acid, and the major urinary metabolite of prostaglandin D 2 [22, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…measurements of mast cell mediators, should be sought in mastocytosis, but random analysis of the urinary histamine levels was not proven useful for establishing the diagnosis. Only 1–3% of histamine appears unmetabolized in the urine, but there may be an increase in the major urinary histamine metabolites, N T -methyl-histamine and 1-methyl-4-imidazoleacetic acid, and the major urinary metabolite of prostaglandin D 2 [22, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the histamine metabolites N-methylhistamine and methylimidazoleacetic acid in 24-hour urine specimens are the preferred method of assessment of baseline histamine levels in patients [9]. The levels of these metabolites appear to correlate with the amount of mast cell burden [10]. One study, however, found serum tryptase levels to be a more sensitive indicator of limited disease [11].…”
Section: Markers Associated With the Mast Cell Granule Or Constitutivmentioning
confidence: 99%
“…Patients with systemic mastocytosis appear to have altered metabolism of histamine Diagnosis causing a disproportionate increase of Nt-methylhistamine and Nt-methylimidazoleacetic acid in urine. In addiIf mastocytosis is suspected on clinical grounds, the evaluation should include clinical and histological exam-tion to being a reliable way of assessing the extent of systemic involvement, measurement of these metabolites ination of skin, complete blood count with differential, 24-hour urine collection for measurement of mediators periodically can be used to monitor disease activity [62,64]. Serum PGD 2 measurement is also plagued by and a bone marrow aspirate and biopsy.…”
Section: Mastocytosis -A Disease Characterized By An Increasedmentioning
confidence: 99%